SUSTAINABLE TOURISM MANAGEMENT MODEL FOR TEGENUNGAN WATERFALL, GIANYAR - Ni Made Sudarmini; Cokorde Istri Sri Widari; Ni Wayan Sukartini (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
In general, the aim of this research was to design a model for the management of Tegenungan waterfall attraction located in Gianyar regency. The data were gathered through interviews, observation, questionnaire, and documentation. Data analysis was conducted using descriptive statistics, adopting a descriptive qualitative method. The findings of the study are expected to be useful for the management, local society, government, and Politeknik Negeri Bali. The results of the data analysis showed that the management model suitable to be applied to operate the Tegenungan Waterfall attraction pointed to the establisment of the Tegenungan Waterfall Attraction Management Board which should involve four stakeholders, namely community, businessmen, government, and universities. Suggestions to improve the management of Tegenungan waterfall attraction are as follows: (1) Tegenungan Village should improve their management system through establishing Tegenungan Waterfall Tourism Object Management Board by appointing an operational manager capable of running the attraction professionally; improving supporting facilities; conducting promotion; establising cooperation with other parties. (2) The government should issue a regulation which governs sand digging around Petanu river which is the source of the Tegenungan waterfall (3) in accordance with its third principle, that is community service, university should train the villagers, through management workshop, how to effectively run the waterfall attraction